A note on firm age and the margins of imports: First evidence from Germany - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
This note uses a new tailor-made data set to investigate the link between firm age and the extensive margins of imports empirically for the first time for Germany. Results turn out to be fully in line with the theoretical considerations. Older firms are more often importers, import more different goods, and import from more different countries of origin.
Keywords: F14; 330; Imports; firm age; import margins; Germany